2020
DOI: 10.22219/jibe.v4i02.12954
|View full text |Cite
|
Sign up to set email alerts
|

Factor affecting user satisfaction in agricultural e-commerce applications: Facing the new normal

Abstract: Agricultural E-Commerce with a retail business model has a big challenge to become an alternative sales distribution of agricultural products. Consumer satisfaction and loyalty can be a strategy for companies to maintain and increase sales. The purpose of this study was to analyze the users of agricultural e-commerce application characteristics and variables that affect customer satisfaction and loyalty. It was conducted by a survey in the Greater Jakarta area, Indonesia. Research data were collected using a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(17 reference statements)
0
0
0
1
Order By: Relevance
“…These are loyal customers whose experience with a product exceeds their expectations and will provide very positive word of mouth about a product to others. So orange marketers must strive hard to create and design strategies to do so in order to gain customer loyalty (Do et al, 2023;Liang et al, 2008;Nusifera et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…These are loyal customers whose experience with a product exceeds their expectations and will provide very positive word of mouth about a product to others. So orange marketers must strive hard to create and design strategies to do so in order to gain customer loyalty (Do et al, 2023;Liang et al, 2008;Nusifera et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This services that in accordance with their expectations a positive experience is formed by resulting in customer's satisfaction and desires to repurchase the products and reuse the services. Moreover, according to (Nasser et al, 2015) there is a significant difference between the online and offline market. Customers make purchases through the website so that companies should develop attractive information on the website.…”
Section: Part 2: Discussionmentioning
confidence: 99%
“…The factors that influence user satisfaction in agricultural e-commerce applications were studied by A.N. Nusifera et al (2020). Their study found that most agricultural e-commerce users were women in their 20s and 30s, often married and well-educated.…”
Section: Discussionmentioning
confidence: 99%